Ion-beam modification of composite based on multi-walled carbon nanotubes and tin dioxide - P. M. Korusenko (Омский научный вестник)
Using the methods of transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDA), and X-ray photoelectron spectroscopy (XPS), there are analyzed changes in the morphology, phase composition, and chemical state of a composite based on multiwalled carbon nanotubes and tin oxide (SnO2 /MWCNTs) modified by pulsed ion beam of nanosecond duration. It is shown that irradiation of the composite leads to a change in the chemical state of nanoparticles of tin oxide, their redistribution and fixation on the surface of MWNTs. A significant decrease in the average size of tin oxide nanoparticles from ~120 nm to ~15 nm is established, which is explained by the heating, dissociation and evaporation of SnO2 under the action of an ion beam, followed by vapor deposition on the surface of carbon nanotubes.